Step 1: Convert zeros to factors of the polynomial.
If "k" is a zero, then (x-k) is a factor of the polynomial.
The allows us to convert zeros of -3, -1, and 2 into the factors (x+3)(x+1)(x-2).
So right now we have y= (x+3)(x+1)(x-2), but there's a missing piece, the leading coefficient of "a", so really we currently have
y = a · (x+3)(x+1)(x-2)
This is where the point (3,5) comes in. We need to substitute x=3 and y=5 into the equation above to find a.
5 = a · (3+3)(3+1)(3-2)
5 = a · (6)(4)(1)
5 = a · 24
5/24 = a
That's the full function:
f(x) = 5/24 (x+3)(x+1)(x-2)